2003
DOI: 10.1038/sj.bmt.1704202
|View full text |Cite
|
Sign up to set email alerts
|

A randomised study of 10 μg/kg/day (single dose) vs 2 × 5 μg/kg/day (split dose) G-CSF as stem cell mobilisation regimen in high-risk breast cancer patients

Abstract: A randomised study of 10 lg/kg/day (single dose) vs 2 Â 5 lg/kg/day (split dose) G-CSF as stem cell mobilisation regimen in high-risk breast cancer patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…These reports indicated that a higher baseline G‐CSF serum level may be important for enhancing CD34+ cell mobilization in normal, healthy donors 13 . A split‐dose G‐CSF regimen, however, does not always enhance PBPC mobilization in patients with malignancies 14‐16,21 . By contrast, another report indicates that increasing the G‐CSF dose allows PBPC collection in patients failing PBPC mobilization, indicating the importance of a higher peak concentration of G‐CSF for PBPC mobilization in patients with malignancies 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports indicated that a higher baseline G‐CSF serum level may be important for enhancing CD34+ cell mobilization in normal, healthy donors 13 . A split‐dose G‐CSF regimen, however, does not always enhance PBPC mobilization in patients with malignancies 14‐16,21 . By contrast, another report indicates that increasing the G‐CSF dose allows PBPC collection in patients failing PBPC mobilization, indicating the importance of a higher peak concentration of G‐CSF for PBPC mobilization in patients with malignancies 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The higher yield resulting from twice‐daily G‐CSF administration may be due to a higher minimum serum level and therefore to a more continuous serum baseline level, which results in more efficient CD34+ cell mobilization 13 . Trials comparing once‐ and twice‐daily G‐CSF as PBPC mobilization therapy in patients with malignancies, however, have yielded conflicting results 14‐16 …”
mentioning
confidence: 99%
“…44 However, studies comparing a single daily dose versus divided dose of G-CSF showed conflicting results. 5,44 Higher doses of G-CSF (8 to 12 µg/kg/12h) resulted in the collection of a higher number of CD34 + cells with fewer apheresis procedures, suggesting the existence of a dose-effect response. [45][46][47] The use of G-CSF has the advantage of allowing the mobilization planning, resulting in more predictability, when compared to chemotherapy.…”
Section: Measurement Of Cd34+ Cell Count In Peripheral Bloodmentioning
confidence: 99%
“…4 Even though they are well established in everyday practice of Hematology and Transplant centers, mobilization regimens can vary greatly from one institution to another and differ in terms of clinical and pharmacoeconomic outcomes. [5][6][7] Of the currently available regimens, the one most commonly used involves the isolated use of the granulocyte-colony stimulating factor (G-CSF), which has the advantages of being well tolerated and allowing the programming of apheresis procedures. 8,9 The combination of chemotherapy and G-CSF has shown to improve the collection of CD34 + cells and reduce tumor activity, but at the expense of increased risk of complications such as fever and neutropenia.…”
Section: Introductionmentioning
confidence: 99%
“…The recommended dose of G-CSF after chemotherapy is 5 mg/kg/d. 16 Increasing the dose of G-CSF to more than 5 mg/kg/d 17,18 or changing the administration schedule 19 has not been proven to improve PBPC mobilization. The use of a single dose of pegfilgrastim was demonstrated as equivalent to a daily administration of filgrastim for mobilizing PBPC.…”
mentioning
confidence: 99%